Preoperative differential diagnosis – uterine sarcoma or myoma? - Lepoivre, Cloé; Kajdos-Wągrowska, Magdalena; Cholewa-Nowak, Karolina; Oleś, Dominik; Nowak, Marek (Menopause Review/Przegląd Menopauzalny, 2025)
Uterine leiomyosarcoma (uLMS) is a rare, heterogeneous, and aggressive tumour, representing only 2–5% of all uterine neoplasms. It poses a significant diagnostic and therapeutic challenge due to symptom overlap with benign uterine conditions such as uterine fibroids. Risk factors of uLMS include advanced age, larger tumour size, submucosal localisation, prior malignancies, tamoxifen use, pelvic radiation, and higher body mass index. This review analyses 13 studies to better identify preoperative indicators of leiomyosarcoma and highlights the challenges in differentiating malignant tumours from benign fibroids. Early detection remains difficult because the clinical presentation often mimics more common benign conditions, leading to delays in diagnosis and treatment. Current diagnostic methods: clinical examination, ultrasound, magnetic resonance imaging (MRI), and histopathology, offer important clues such as tumour size, irregular margins, necrosis, and vascular patterns, but none offers definitive preoperative diagnosis. While advanced imaging techniques like dynamic MRI show promise in distinguishing uLMS from leiomyomas, these methods are not yet practical for routine use. Blood markers lack diagnostic reliability. Minimally invasive surgical procedures, such as laparoscopic power morcellation, carry risks of spreading occult malignancies and should only be performed in carefully selected patients. Therefore, comprehensive preoperative evaluations and improved diagnostic tools are critical to facilitate earlier detection and optimise treatment outcomes, particularly in high-risk populations. Increased awareness among healthcare providers and patients is essential for improving prognosis and reducing the incidence of late-stage presentations.